Computer-aided architectural design : future trajectories : 17th International Conference, CAAD Futures 2017, Istanbul, Turkey, July 12-14, 2017, Selected papers /: future trajectories : 17th International Conference, CAAD Futures 2017, Istanbul, Turkey, July 12-14, 2017, Selected papers. (2017) - Unknown
No abstract available